2021
DOI: 10.3390/biomedicines9111575
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides Involved in Facial Nerve Regeneration

Abstract: Neuropeptides and neurotransmitters act as intermediaries to transmit impulses from one neuron to another via a synapse. These neuropeptides are also related to nerve degeneration and regeneration during nerve damage. Although there are various neuropeptides, three are associated with neural regeneration in facial nerve damage: calcitonin gene-related peptide (CGRP), galanin, and pituitary adenylyl cyclase-activating peptide (PACAP). Alpha CGRP in facial motoneurons is a signaling factor involved in neuroglial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The molecular response of damaged motor neurons following facial nerve injury involves the upregulation of early genes followed by the expression of neuromodulatory and regeneration-related genes [107]. Calcitonin gene-related peptide (CGRP) is among the early representative genes upregulated in facial nerve nuclei, together with c-Jun and growth-associated protein-43 (GAP-43) [24].…”
Section: Calcitonin Gene-related Peptide and Growth-associated Protei...mentioning
confidence: 99%
“…The molecular response of damaged motor neurons following facial nerve injury involves the upregulation of early genes followed by the expression of neuromodulatory and regeneration-related genes [107]. Calcitonin gene-related peptide (CGRP) is among the early representative genes upregulated in facial nerve nuclei, together with c-Jun and growth-associated protein-43 (GAP-43) [24].…”
Section: Calcitonin Gene-related Peptide and Growth-associated Protei...mentioning
confidence: 99%
“…Among the aforementioned mediators, neuropeptides have been widely studied in the last four decades. Neuropeptides are neurotransmitters composed of amino acids linked by peptide bonds 8 . After sensory neurons are stimulated, neuropeptides are released from nerve terminals or synaptic clefts and act directly on neurons (nociceptors, TG, and SpVc) or non‐neuronal targets (glial cells, endothelial cells and inflammatory cells), thereby contributing to neurogenic inflammation and orofacial pain.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropeptides are neurotransmitters composed of amino acids linked by peptide bonds. 8 After sensory neurons are stimulated, neuropeptides are released from nerve terminals or synaptic clefts and act directly on neurons (nociceptors, TG, and SpVc) or non-neuronal targets (glial cells, endothelial cells and inflammatory cells), thereby contributing to neurogenic inflammation and orofacial pain. Previous studies have demonstrated that neuropeptides, including calcitonin generelated peptide (CGRP), 4 substance P (SP), 9 opioid peptides (OP), 10 galanin (GAL), 11 vasoactive intestinal peptide (VIP), 12 neuropeptide Y (NPY), 13 neurokinin A (NKA), 14 orexin-A (OrxA) 15 and oxytocin (OXT), 16 are involved in orofacial pain.…”
mentioning
confidence: 99%